2020
DOI: 10.7554/elife.57670
|View full text |Cite
|
Sign up to set email alerts
|

Neural signatures of α2-Adrenergic agonist-induced unconsciousness and awakening by antagonist

Abstract: How the brain dynamics change during anesthetic-induced altered states of consciousness is not completely understood. The α2-adrenergic agonists are unique. They generate unconsciousness selectively through α2-adrenergic receptors and related circuits. We studied intracortical neuronal dynamics during transitions of loss of consciousness (LOC) with the α2-adrenergic agonist dexmedetomidine and return of consciousness (ROC) in a functionally interconnecting somatosensory and ventral premotor network in non-huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
(99 reference statements)
0
12
0
Order By: Relevance
“…Thus, for instance, the ability to infer the current state of one channel by observing the state of a nearby channel in the cortex is limited. Remarkably, we provide evidence that abrupt transitions between discrete macroscopic cortical activity patterns (Ballesteros et al, 2020;Chander et al, 2014;Hudson et al, 2014;Ishizawa et al, 2016;Lee et al, 2020;Patel et al, 2020) emerge naturally from the multitude of these quasi-independent local fluctuations. We also demonstrate that the strength of the interactions between recording sites depends on the inter-electrode distance and on the cortical layer.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Thus, for instance, the ability to infer the current state of one channel by observing the state of a nearby channel in the cortex is limited. Remarkably, we provide evidence that abrupt transitions between discrete macroscopic cortical activity patterns (Ballesteros et al, 2020;Chander et al, 2014;Hudson et al, 2014;Ishizawa et al, 2016;Lee et al, 2020;Patel et al, 2020) emerge naturally from the multitude of these quasi-independent local fluctuations. We also demonstrate that the strength of the interactions between recording sites depends on the inter-electrode distance and on the cortical layer.…”
Section: Discussionmentioning
confidence: 71%
“…These data suggest that global brain states comprise regionally distinct oscillation patterns that are weakly coupled with one another. Remarkably, these results show that discrete transitions between global cortical states (Ballesteros et al, 2020;Hudson et al, 2014;Patel et al, 2020) under a fixed anesthetic concentration arise from the multitude of weakly coupled local fluctuations.…”
Section: Pc1 V1l V1rmentioning
confidence: 71%
“…It has been suggested that the locus coeruleus–norepinephrine (LC-NE) system plays a key role in sensory signal processing to facilitate information integration such as decision making and motor response [ 25 , 26 ]. Most studies generally claim that LC-NE activation facilitates the representation of sensory signals by inhibiting spontaneous neuronal activity more than sensory-evoked response, effectively enhancing the signal-to-noise ratio (SNR) at the population level [ 27 , 28 ]. In addition, the ventral tegmental area-dopamine (VTA-DA) system has also been reported as an important target involved in dexmedetomidine-induced sedation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential sedative effects through the thalamus α2-AR agonists can produce sedation, which is a side effect when used to treat ADHD, but helpful when used as an anesthetic, e.g., dexmedetomidine [151]. While presynaptic α2A-AR actions appear to contribute to a sleep state [152], they are unlikely the whole story in primates, as the α2A-AR selective agonist, guanfacine, has little sedative actions, while the very sedating dexmedetomidine is a full agonist at the α2B-AR subtype, and only a partial agonist at the α2A-AR and the α2C-AR subtypes (Table 1) [153].…”
Section: Strengthening and Protection Of Prefrontal Cortexmentioning
confidence: 99%